The rare genera Picacharops Gauld and Sliochia Gauld (Hymenoptera, Ichneumonidae, Campopleginae) found in China, with description of two new species - Han, Yuan-Yuan; Achterberg, Kees Van; Chen, Xue-Xin (Zootaxa, 2022)
Two rare genera are newly reported for China: the Australasian Picacharops Gauld, 1984 and the Oriental Sliochia Gauld, 1976. A new species of these two monotypic genera (P. granulosus sp. nov. and S. adustifemur sp. nov., respectively) is described from China and illustrated. Keys to species of both genera are also provided.